The Implementation of Wordwall Media to Facilitate Students’ Understanding of The Use of的de，地 De, And 得de in Constructing Simple Mandarin Sentences at Vocational High School - Nadzifah, Hidayatun; Pairin, Udjang; Indarti, Titik; Laily, Ulul (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
Technological advances have influenced various fields, including education, which is now increasingly utilizing learning media to make the learning process easier. The use of learning media can stimulate students to think, feel, and increase their interest and attention through the messages conveyed. In this study, Wordwall digital media was used in languge learning to facilitate students in constructing simple Mandarin sentences. This research aims to evaluate the effectiveness of the implementation of Wordwall media on the use of 的 (de), 地 (de), and 得 (de) in constructing simple Mandarin sentences. This research was conducted on class X students at SMK Sunanul Muhtadin Sidayu Gresik using a qualitative descriptive approach. Data was observation, interviews, document collection, and questionnaires via Google Form. The research results show that the use of Wordwall media is very effective in making it easier for students to understand the use of 的 (de), 地 (de), and 得 (de) in constructing simple Mandarin sentences.